The Adoption of Technology in Auditing among Auditors in Pathum Thani Province - กาลวารีย์, กมลพรรณ; ทวีวงษ์, มินตรา; อาดำ, อลิต้า; กาเฮง, อนุศรา; ทองเรือนดี, นพัชกร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the application of technology in auditing in terms of decision-making support, skills, efficiency, and quality; 2) compare the application of technology in auditing classified by gender, age, work experience, and professional status; and 3) propose guidelines for technology-based auditing. The sample consisted of 30 auditors in Pathum Thani Province. Data were collected using questionnaires and interviews. Statistical analyses included percentage, mean, standard deviation, t-test, F-test, and pairwise comparisons using Scheffe’s method.          The findings revealed that: 1) the overall level of technology adoption in auditing was at a high level. When considered by dimension, all aspects were rated at a high level, with efficiency ranking highest, followed by decision-making support, quality, and skills. 2) The comparative analysis indicated that auditors with different genders, ages, work experiences, and professional statuses demonstrated significantly different overall levels of technology adoption in auditing at the .05 level of statistical significance. When examined by dimension, significant differences were found in skills, efficiency, and quality. 3) Auditors should apply digital technologies in analyzing and examining data to support decision-making, while concurrently developing technological competencies and strengthening professional judgment in order to enhance work efficiency and elevate audit quality in accordance with professional standards.